2000
DOI: 10.1037/0278-6133.19.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, correlates, and barriers to medication adherence among persons prescribed new treatments for HIV disease.

Abstract: New treatments for HIV can improve immune functioning and decrease mortality. However, lapses in adherence may render these complex regimens ineffective. Sixty-three men and 9 women on highly active antiretroviral therapy completed measures of medication adherence, psychological characteristics, and barriers to adherence. HIV viral load, a health outcome measure of virus amount present in blood, was also obtained. The sample was 36% African American and 56% Caucasian, with 35% reporting disability. Nearly one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
415
5
13

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 597 publications
(471 citation statements)
references
References 36 publications
38
415
5
13
Order By: Relevance
“…Self efficacy and depression were directly related to adherence, and self-efficacy was found to have a weak indirect relationship to adherence through its association with depression. These relationships lend further support to previous studies that have investigated both the role of self-efficacy and depression on medication adherence (Catz et al 2000;Gonzalez et al 2004;Kleeberger et al 2004). Moreover, the results provide support for self-efficacy theory.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Self efficacy and depression were directly related to adherence, and self-efficacy was found to have a weak indirect relationship to adherence through its association with depression. These relationships lend further support to previous studies that have investigated both the role of self-efficacy and depression on medication adherence (Catz et al 2000;Gonzalez et al 2004;Kleeberger et al 2004). Moreover, the results provide support for self-efficacy theory.…”
Section: Discussionsupporting
confidence: 87%
“…Self-efficacious people are more successful in performing specific behaviors because they are more likely than others to persevere even under difficult situations until their goals are achieved. The results of several studies examining ART adherence support the relationship between self-efficacy and adherence in which higher levels of self-efficacy correspond to higher rates of ART adherence (Catz et al 2000;Gifford et al 2000;Tuldra et al 1999).…”
Section: Theoretical Perspectivementioning
confidence: 76%
See 1 more Smart Citation
“…For example, drug users continue to face discrimination from some medical providers who frequently treat them with distrust and disrespect (Chitwood, Sanchez, Comerford, & McCoy, 2001;Crofts, Louie, & Loff, 1997;Day, Ross, & Dolan, 2003;Edlin et al, 2001;Stephenson, 2001;Treloar, Hopwood, & Loveday, 1996;Zickmund, Hillis, Barnett, Ippolito, & LaBrecque, 2004). Also, despite the recent changes to the NIH guidelines regarding HCV treatment, many health care providers have historically been concerned that drug users treated for HCV might have a high risk of re-infection, low treatment compliance, and/or drug relapse (Catz, Kelly, Bogart, Benotsch, & McAuliffe, 2000;Golub et al, 2004;Gordillo, del Amo, Soriano, & Gonzalez-Lahoz, 1999;Hauser et al, 2002;Milby et al, 1996;Osher et al, 2003). In fact, recent research conducted by Morrill et al (2005) found that primary care physicians tended not to treat patients with a past history of substance abuse for their HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although linking seropositive persons to care is an important goal in itself, increasing the proportion of infected individuals who are referred to and followup in care will also help to decrease rates of HIV transmission. Viral load is often decreased among persons who are linked to care and adhere to their treatment regimens (36,(77)(78)(79); lower viral load is associated with decreased rates of HIV transmission (38)(39)(40)(41).…”
Section: Shifting Context Of Hiv Testingmentioning
confidence: 99%